2020
DOI: 10.1111/jce.14716
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with silent cerebral events during atrial fibrillation ablation in patients on uninterrupted oral anticoagulation

Abstract: Introduction Silent cerebral events (SCEs) are related to the potential thromboembolic risk in atrial fibrillation (AF) ablation. Periprocedural uninterrupted oral anticoagulation (OAC) reportedly reduced the risk of SCEs, but the incidence still remains. Methods and Results AF patients undergoing catheter ablation were eligible. All patients took non–vitamin K antagonist oral anticoagulants (NOACs; n = 248) or vitamin K antagonist (VKA; n = 37) for periprocedural OAC (>4 weeks) without interruption during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
5
9
0
Order By: Relevance
“…While implant recapture to adjust position after deployment is not typically a lengthy process, the decision to proceed with this step may require significant consultation and additional imaging, which, if required, can substantially prolong the procedure time. This observation supports the hypothesis that optimized coaxiality and assessment of LAA size can support more efficient and effective LAAC, thereby reducing safety risks that may be associated with excess device and catheter manipulations 13,15,16 . While other dedicated RF transseptal puncture technologies have been shown to be effective, 11,14 to our knowledge this is the only study where a RF wire‐based system improved LAAC procedural efficiency in addition to a more favorable transseptal time.…”
Section: Discussionsupporting
confidence: 72%
“…While implant recapture to adjust position after deployment is not typically a lengthy process, the decision to proceed with this step may require significant consultation and additional imaging, which, if required, can substantially prolong the procedure time. This observation supports the hypothesis that optimized coaxiality and assessment of LAA size can support more efficient and effective LAAC, thereby reducing safety risks that may be associated with excess device and catheter manipulations 13,15,16 . While other dedicated RF transseptal puncture technologies have been shown to be effective, 11,14 to our knowledge this is the only study where a RF wire‐based system improved LAAC procedural efficiency in addition to a more favorable transseptal time.…”
Section: Discussionsupporting
confidence: 72%
“…Nagao et al 13 demonstrated the average time required for achieving a target ACT >300 seconds was significantly longer in the dabigatran and apixaban groups than in the warfarin and rivaroxaban groups, although these findings are discrepant to the present study results. In accordance with our findings, Harada et al 14 showed a longer time to reach ACT >300 seconds in the rivaroxaban and apixaban groups than the dabigatran, edoxaban, and warfarin groups. In the present study, furthermore, we first addressed the different stabilities using ACT‐TTR during the ablation procedure according to OAC.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding silent cerebral events, Nagao et al 19 reported a significantly higher incidence of silent stroke during the ablation procedure in the dabigatran group than in the other DOACs under uninterrupted use. Meanwhile, Harada et al 14 reported that silent cerebral events during the procedure were associated with higher age, larger left atrial dimension, lower baseline ACT, and longer time to reach optimal ACT in multivariate analysis, but the event rate was not different according to OAC groups. Silent cerebral events also depend on types of ablation devices and procedure time, and bleeding complications greatly depend on operator skills 20–22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that dabigatran is more sensitive to activated clotting time (ACT) assays compared with other DOACs. [35][36][37] The Remote Period After CA The RYOUMA registry also provides valuable data on the continuation of OAC and outcomes during the remote period after CA. At 1 year after CA, DOAC therapy was continued in 55.9% of patients and warfarin therapy in 56.4% of patients.…”
Section: Outcomes During the Remote Periodmentioning
confidence: 99%